2001
DOI: 10.1007/s11883-001-0052-5
|View full text |Cite
|
Sign up to set email alerts
|

Low-density lipoprotein apheresis in the treatment of atherosclerosis and other potential uses

Abstract: This review concerns the clinical impact of low-density lipoprotein (LDL) apheresis for patients with refractory hypercholesterolemia. We examine and provide examples of investigations that have demonstrated the clinical benefits of LDL apheresis. In addition to benefits derived from the stabilization or regression of arterial lesions, we highlight other possible mechanisms related to clinical improvement. We also discuss the potential advantages of lipid apheresis for the treatment of patient populations othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…For example, in patients with atherosclerosis, long-term LDL-apheresis slowed the progression of carotid intima-media thickness (CIMT). The suggestion is that beneficial effects in vascular function could be derived from apheresis-related effect on rheological parameters or by increasing (directly or indirectly) lipoprotein lipase activity (12) . Based on this we hypothesized that at post-LDLapheresis status the homozygous and heterozygous patients will have similar lipid profile, which will provide a condition to compare other parameters demonstrating the endothelial functions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in patients with atherosclerosis, long-term LDL-apheresis slowed the progression of carotid intima-media thickness (CIMT). The suggestion is that beneficial effects in vascular function could be derived from apheresis-related effect on rheological parameters or by increasing (directly or indirectly) lipoprotein lipase activity (12) . Based on this we hypothesized that at post-LDLapheresis status the homozygous and heterozygous patients will have similar lipid profile, which will provide a condition to compare other parameters demonstrating the endothelial functions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, definitive recommendations have been published by various national as well as international societies and organizations [2831]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, homocysteine may be one of the mechanisms involved in endothelial and monocyte stimulation. In addition, we demonstrated that, even at a distance of 6 months from the acute event, in patients with a previous myocardial infarction two important elements are detectable: first, a remarkable clotting activation – which seems to be related, at least in part, to homocysteine levels – and second, high levels of TF, which mirror the persistent activation status of monocytes [24,25].…”
Section: Discussionmentioning
confidence: 99%